Nature’s Pharmacy: Plant-Based Antifungal Agents and Their Therapeutic Potential - Ashish Yadav; Himanshu Singh; Rajkamal; Nitish Kumar; Raveena Rani (International Journal of Tropical Medicines, 2026)
Antifungal resistance has increased dramatically over the last 10 years, causing serious problems for healthcare because of higher morbidity and death. The urgent need for new treatments is highlighted by the scarcity of effective antifungal medications, their toxicity, and the rise of resistant strains. Since many plants have bioactive secondary metabolites with strong antifungal qualities, including alkaloids, flavonoids, terpenoids, phenolics, and saponins, ethnobotanical sources offer a viable path. Plants with notable antifungal action, such as Bridelia retusa, Hypoestes serpens, and Piper crassinervium, have been used in traditional medicine. These phytochemicals work by causing oxidative stress, blocking ergosterol synthesis, and rupturing fungal membranes. Recent developments in nanotechnology have improved the clinical potential of plant-derived chemicals by increasing their stability, bioavailability, and targeted delivery. Nevertheless, issues with bioavailability, standardization, and regulatory approval still exist. Finding safe, efficient, and long-lasting antifungal medicines to counteract growing resistance may be made easier by combining ethnobotanical knowledge with contemporary scientific study.
Keywords: Antifungal resistance; Bridelia retusa; Flavonoids; Hypoestes serpens; Phytochemicals; Piper crassinervium; Plant-derived antifungal agents; Terpenoids; nanotechnology